2016
DOI: 10.1002/tie.21878
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Paths from Export Strategic Orientations to Export Performance: The Mediating Role of Export Resource Transformation Capability

Abstract: Export strategic orientation research suggests that export entrepreneurial orientation ( EO ) and market orientation ( MO ) directly affect export performance. Based on the dynamic capability theory, this study hypothesizes that export resource transformation capability is an intervening factor that helps explain how EO and MO , individually and jointly, impact export performance. Using archival and survey data from small and medium-sized exporters in the United Kingdom and Nigeria, the study fi nds that expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 96 publications
(168 reference statements)
7
42
0
Order By: Relevance
“….91 (17.98) Industry: industry type of the firm .77 (13.03) Export sales: annual export sales of the firm .75 (12.40) Fit indices: χ 2 = 587.59; df = 221, p < .001; NFI = .93, NNFI = .95; CFI = .96; RMSEA = .08 NFI: normed fit index; NNFI: nonnormed fit index; CFI: comparative fit index; RMSEA: root mean square error approximation. Mackinnon et al's (2002) recommendation to test the mediation model hierarchically (Boso et al, 2018b;Lu et al, 2009). First, we examined the full mediation model (baseline model) which does not have a path from independent variable (i.e.…”
Section: Construct and Details Of Measuresmentioning
confidence: 99%
“….91 (17.98) Industry: industry type of the firm .77 (13.03) Export sales: annual export sales of the firm .75 (12.40) Fit indices: χ 2 = 587.59; df = 221, p < .001; NFI = .93, NNFI = .95; CFI = .96; RMSEA = .08 NFI: normed fit index; NNFI: nonnormed fit index; CFI: comparative fit index; RMSEA: root mean square error approximation. Mackinnon et al's (2002) recommendation to test the mediation model hierarchically (Boso et al, 2018b;Lu et al, 2009). First, we examined the full mediation model (baseline model) which does not have a path from independent variable (i.e.…”
Section: Construct and Details Of Measuresmentioning
confidence: 99%
“…For instance, Boso, et al [94]; Jing and Zhu [95] suggested the third variable can be moderating or mediating variable on the relationship between EMO and FEP. Therefore, in line with the findings of the above literature, it is postulated that there is a need to further investigate the relationship between EMO and FEP, especially the presence of a third variable.…”
Section: Export Market Orientation (Emo) and Firm Export Performance mentioning
confidence: 99%
“…Therefore, firms are required to adopt an entrepreneurial posture to outperform their rivals in the marketplace and achieve a superior performance (Ireland et al 2003, Kuratko andAudretsch 2013;Morris et al 2011;Wales 2016;Zahra 1993). The role entrepreneurship has been scrutinized on innovation performance, firm performance in both domestic and international business context, firm capabilities including innovation, marketing and learning capabilities (Boso et al 2018;Genc et al 2019;Monteiro et al 2019).…”
Section: Related Issuesmentioning
confidence: 99%
“…An entrepreneurial firm prioritizes its innovative functions, undertaking risky actions, employing autonomy, engaging proactive actions, and compete aggressively towards its rivals in the market. In the literature, a complementary line of studies addressed the role entrepreneurial orientation on firm performance by asserting that firms that pursue entrepreneurial proclivity can achieve outstanding performance in their business environments (Boso et al 2018;Kantur 2016;Lisboa et al 2016). Although there is still a proliferating pattern in entrepreneurial orientation research, there are still ongoing discussions about its conceptualization.…”
Section: Introductionmentioning
confidence: 99%